1995
DOI: 10.1093/infdis/171.3.531
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Function In Vitro Is An Independent Progression Marker For Aids In Human Immunodeficiency Virus-Infected Asymptomatic Subjects

Abstract: The predictive value of low T cell reactivity to CD3 monoclonal antibodies for development of AIDS was evaluated and compared with low CD4+ cell numbers and the presence of syncytium-inducing human immunodeficiency virus (HIV) variants in 122 seropositive asymptomatic homosexual men for 4.5 years. Low T cell reactivity was a strong predictor for progression to AIDS in a multivariate proportional hazards analysis using these markers as covariates at entry and as time-dependent covariates. The combination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…In previous studies we demonstrated that in HIV-1 infection T cell reactivity to soluble CD3 MoAb measured in whole-blood lymphocyte cultures is an independent prognostic marker for progression to disease [12,23]. However, T cell responses to CD3 MoAb are relatively low with a tendency to have high coefficients of variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies we demonstrated that in HIV-1 infection T cell reactivity to soluble CD3 MoAb measured in whole-blood lymphocyte cultures is an independent prognostic marker for progression to disease [12,23]. However, T cell responses to CD3 MoAb are relatively low with a tendency to have high coefficients of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expansion of CD8 CD28 ÿ cells was not specific for HIV-1 because this expansion was already seen in HIV -homosexual men at high risk. As we reported before, it is well feasible to test T cell reactivity to PHA and CD3 MoAb in whole-blood lymphocyte culture assays [12,23,32]. This is a simple, reproducible and suitable method for large routine screening/ monitoring of cohorts and patients enrolled in anti-retroviral drug trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell proliferative capacity is an important independent predictor of progression to HIV disease [35,36] and can also serve to monitor immunological improvement after therapy [37,38]. Decreased proliferation of T-cells from HIV-infected individuals has been previously measured in response to in-vitro stimulation with CD3 monoclonal antibody, pokeweed mitogen, alloantigens, and recall antigens [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of the AIDS epidemic, P. carinii pneumonia (PCP) 4 was a major cause of death in HIV-infected individuals. Today, the emergence of drug-resistant strains of HIV, the toxicity of antiretroviral agents, and economic factors limit both access to and the effectiveness of antiretroviral therapies, resulting in a large population of HIV-infected patients worldwide who are susceptible to PCP (2).…”
mentioning
confidence: 99%